WS-BPEL 2.0 for SOA composite applications with IBM WebSphere 7 : define, model, implement, and monitor real-world BPEL 2.0 business processes with SOA-powered BPM /: define, model, implement, and monitor real-world BPEL 2.0 business processes with SOA-powered BPM. (©2010) - Unknown
No abstract available